Pembentukan Kanji Jukujikun (熟字訓) dalam Manga One Piece - Azizah, Rinamaryama Amanatul; Rosiah, Rosi (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2026)
This study aims to identify and analyze the formation and meaning of the inter-element kanji jukujikun found in One Piece manga volume 113 by Eiichiro Oda. This study is important because jukujikun has a special reading system that cannot be understood only through its constituent elements. The method used is a descriptive qualitative method with literature review techniques. The results of the study show that there are 11 jukujikun: 2 consisting of a single kanji, 7 consisting of two kanji, and 2 consisting of three kanji. From these data, 7 jukujikun are included in the type of formation of the ‘pemeri’ relationship, and 2 jukujikun are included in the type of formation of two core kanji followed by one single kanji. The results of the analysis confirm that the formation of jukujikun is not only determined by the structure of kanji, but also by the wago factor/native Japanese vocabulary, so that its meaning is layered.